Robusta coffee (Coffea canephora) value chain in East Java, Indonesia - Winarno, Sri Tjondro (2022)
Introduction. Coffee plantations are one of the growing agriculture sub-sectors and a high coffee production should be based on proper processing and marketing. Objective. To analyze the updates of products, processes, functions, and upgrading of the robusta coffee value chain in East Java. Materials and methods. This study was conducted in the Robusta coffee plantations in the Bondowoso, Jember, Lumajang, Pasuruan, Malang, and Ngawi districts in East Java, Indonesia, between October 2019 and March 2020. The quota sampling technique was used, followed by surveys and interviews. The number of respondents was 120 people who were actors in the coffee value chain, such as farmers, coffee cherry collectors, coffee cherry grinders, green bean grinders, and consumers. Results. The results showed that product, function, and channel upgrading had a significant effect on the coffee value chain, but the upgrading process did not significantly affect it in several regions on East Java. Conclusions. There is a need for innovation to enhance the coffee value chain in order to deliver future benefits to all stakeholders in this market.